“TEKO BERSAYAP” MODEL SOLAR DRYER FOR FISH DRYING - Yuwana Yuwana; Bosman Sidebang; Evanila Silvia (Jurnal Agroindustri, 2016)
This objective of this research was to design a dryer called “Teko Bersayap” model and then to test its performance in drying fish in order to solve problems arising from open air sun drying. The dryer consisted of drying chamber with trays inside, heat collectors equipped with air inlets at their lower ends, chimney with an exhaust fan inside and humid air outlet at its upper end, was constructed to dry fish, “Bleberan (Pepetak Leiognatus spp)” species. The results of the experiment indicated that the dryer produced the drying chamber temperature 8.83oC higher than the ambient temperature and the relative humidity 13.91% lower than the ambient relative humidity. The fish moisture content decreased exponentially with drying time and the dryer completed the fish drying process in 18.9 hours compared to 27.6 hours of drying time needed to complete the sun drying for the fish, suggesting that the dryer was ready for utilization